(Q, T)-affine-periodic solutions and Pseudo (Q, T)-affine-periodic solutions for Dynamic Equations on Time Scales. (31st March 2022) - Guo, Ruichao; Jiang, Xiaomeng; Wang, Hongren
Abstract : The aim of this paper is to study the existence of Q, T -affine-periodic solutions for affine-periodic systems on time scales of the type x Δ t = A t x t + f t and x Δ t = A t x t + g t, x t, t ∈ T, assuming that corresponding homogeneous equation of this system admits exponential dichotomy. The result is also extended to the case of pseudo Q, T -affine-periodic solutions. The main approaches are based on the Banach contraction mapping principle, but certain technical aspects on time scales are more complicated.